ANALISIS STRATEGI KEUNGGULAN BERSAING DAN BRAND IMAGE DENGAN PENDEKATAN FIVE FORCES PORTER DI RUMAH MAKAN RIUNG PANYAUNGAN - Kundratr; Sumarti, Lily; Fetia Wardhani, Wini; Rahmadia Febryane, Rimelke; Burhanudin; Diana Octaviani, N (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
This study aims to analyze the strategies employed by Riung Panyaungan, a pioneer of Sundanese cuisine in Bandung Regency, established in 1997. The primary focus is to identify existing strategies, evaluate their effectiveness, and provide strategic recommendations to enhance competitive advantage. The methods used include Porter’s Five Forces and Brand Image analysis with a Likert scale. The results indicate that Riung Panyaungan employs a brand identity and marketing-focused strategy, which has proven effective in maintaining operational efficiency and business resilience. The recommended strategy is differentiation to strengthen competitive advantage and sustain its position in the culinary market. Keywords: Riung Panyaungan, differentiation strategy, Porter’s Five Forces, Brand Image, competitive advantage